Cinema's conversion to sound : technology and film style in France and the U.S. - O'Brien, Charles, 1955- (Book collections on Project MUSE., 2005)
The conversion to sound cinema is routinely portrayed as a homogenizing process that significantly reduced the cinema's diversity of film styles and practices. Cinema's Conversion to Sound offers an alternative assessment of synchronous sound's impact on world cinema through a shift in critical focus: in contrast to film studies' traditional exclusive concern with the film image, the book investigates national differences in sound-image practice in a revised account of the global changeover from silent to.